Déterminants des recours thérapeutiques et prise en charge du bétail dans l'ouest du Burkina Faso - Ouédraogo, D.; Kamuanga, M.; Savadogo, K.; McDermott, John J.; Woitag, T. (CAIRN, 2006)
This paper analyzes the strategies of farmers in Kénédougou province to tackle African Animal Trypanosomosis (AAT). Using economic, entomological, and parasitological data collected by mul-tidisciplinary team, we operate a binary Logit model to evaluate the probability of choice between animal health professionals and non professionals. The results show that economic and environmental variables contribute jointly to explain the choice between professional and non professional. The prevalence of trypanosomosis, and farm size affect positively the choice of farmers. However, farmers in crop production systems and producers who are far from the location of animal health professionals are slightly willing to choose their services for AAT control. Animal development policy should pay attention to physically and economic access to trypanocides in order to mitigate the impact of AAT on the productivity of farms.